The failure of the state’s integration policy towards population groups in western and northern Poland after World War II - Osękowski, Czesław (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the effectiveness of the integration policy pursued by the Polish state in the western and northern territories after the Second World War. The author examines the process of creating a new society in areas settled by people with diverse historical, cultural, and social experiences. The aim of the study is to explain the causes of the limited success of integration efforts and to identify factors that perpetuated social divisions. The analysis employs a historical-sociological approach that takes into account migration processes, state policy, and relations among different population groups. The society of the western and northern territories consisted of settlers from central Poland, repatriates from lands annexed by the Soviet Union, returnees from other parts of Europe, displaced Ukrainians, and indigenous inhabitants verified as Poles. The author argues that despite the declared objective of integration, government policies did not facilitate the formation of durable social bonds. The dominance of a single political force, restrictions on democracy, extensive control over public and private life, and the atmosphere of uncertainty after 1945 more often led to disintegration than to social cohesion. Institutions intended to promote integration, such as schools, cultural organizations, and the Church, also proved to be of limited effectiveness. Additional sources of tension included cultural differences and divergent attitudes toward the new place of residence and the western border of the state. The conclusions indicate that the state model of integration relied primarily on administrative coercion and ideology rather than on natural social processes. As a result, it failed to overcome social divisions completely, and its overall effectiveness remained limited.